Análise florística e fitossociológica de fragmentos florestais de Mata Atlântica no sul do Estado do Espírito Santo - Archanjo, Karla Maria Pedra de Abreu (2008)
The objective of this work was to raise and discuss information about arboreal communities of two forest fragments, considering the lack of studies of vegetation of the south of the Espírito Santo state. The fragments are located in the municipal of Cachoeiro de Itapemirim, being the Floresta Nacional (FLONA) de Pacotuba and the Reserva Particular do Patrimônio Natural (RPPN) Cafundó. In FLONA de Pacotuba, the composition floristic consisted of 258 species and in RPPN Cafundó of 258 species, being 111 species common to the two fragments. The richest families in species in FLONA of Pacotuba are: Fabaceae, Sapotaceae, Euphorbiaceae, Myrtaceae and Meliaceae; while in RPPN Cafundó are: Myrtaceae, Fabaceae, Sapotaceae and Euphorbiaceae. In the analysis of the similarity of FLONA de Pacotuba and of RPPN Cafundó, it was demonstrated that in spite of the geographical proximity, the different disturbance reports and regeneration, they resulted in different floristics compositions between these fragments. Being considered the diversity, the index of Shannon-Weaver (H) found in RPPN Cafundó (4,13), reach a more expressive value than the FLONA of Pacotuba (3,31). The value found for equability (J) is 0,60 in FLONA of Pacotuba and 0,74 in RPPN Cafundó. In the horizontal structure of FLONA of Pacotuba, the species Senefeldera verticillata, Actinostemon estrellensis and Anadenanthera peregrina dominate the community in relation to IVI(%); in RPPN Cafundó, the species that more stood out in IVI(%) are: Astronium concinnum, Pseudopiptadenia contorta and Neoraputia alba.The RPPN Cafundó presents larger number of individuals for hectare in the first diameter classes. The diametric structures of the fragments follow the general pattern of the uneven-aged forests, in reversed-J-shape. The vertical structure varies of 2 until 50 meters in FLONA de Pacotuba and of 2,1 until 54 meters in RPPN Cafundó